PENGARUH PUPUK HAYATI TERHADAP PERKEMBANGAN PENYAKIT LAYU FUSARIUM PADA TOMAT - , MARLINA PUSPITA SARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The study aims to determine the ability of Omega biofertilizer to inhibit the vegetative growth of the Fusarium oxysporum f.sp. lycopersici and to suppress infection rate of Fusarium wilt on tomato. Omega biofertilizer is the by product of herbal medicine based on herbal medicine plants. This biofertilizer contains many micro and macro nutrients and beneficial microorganisms to plants. This study was conducted in two tests: in vitro and in vivo. In vitro test was performed by adding 1 ml of Omega biofertilizer, chemical fungicide or sterile water in 9 ml of PDA used to grow the Fusarium oxysporum f.sp. lycopersici. In the in vivo test, inoculation was conducted by soaking the roots before seeds transfering to the pots with conidial density of Fusarium oxysporum f.sp. lycopersici reach 106 cell/ ml. The results showed that Omega biofertilizers affected the vegetative growth of the Fusarium oxysporum f.sp. lycopersici and Fusarium wilt development in tomato. Omega biofertilizer could suppress the development of Fusarium wilt on tomatoes both in vitro and in vivo tests. Vegetative growth of Fusarium oxysporum f.sp. lycopersici on medium mixed with Omega bio-fertilizers was slower compared with other treatments. In the in vivo test, tomatoes treated with Omega biofertilizer had lowest intensity and growth rate of Fusarium wilt disease compared to other treatments. Tomatoes inoculated with Fusarium oxysporum f.sp. lycopersici without treated with Omega biofertilizer or chemichal fungicide, had the highest Fusarium wilt disease intensity, reached 32.29% at 9th week after inoculation.